The Utility of MMPI-2-RF Substantive Scales in Prediction of Negative Treatment Outcomes in a Community Mental Health Center. (February 2015) - Anestis, Joye C.; Gottfried, Emily D.; Joiner, Thomas E.
This study examined the utility of the Minnesota Multiphasic Personality Inventory–2–Restructured Form (MMPI-2-RF) substantive scales in the prediction of premature termination and therapy no-shows while controlling for other relevant predictors in a university-based community mental health center, a sample at high risk of both premature termination and no-show appointments. Participants included 457 individuals seeking services from a university-based psychology clinic. Results indicated that Juvenile Conduct Problems (JCP) predicted premature termination and Behavioral/Externalizing Dysfunction and JCP predicted number of no-shows, when accounting for initial severity of illness, personality disorder diagnosis, therapist experience, and other related MMPI-2-RF scales. The MMPI-2-RF Aesthetic-Literary Interests scale also predicted number of no-shows. Recommendations for applying these findings in clinical practice are discussed.